The role of the WNT/β-catenin pathway in central nervous system primitive neuroectodermal tumours (CNS PNETs) - Rogers, H.A.; Ward, J.H.; Miller, S.; Lowe, J.; Coyle, B.; Grundy, Richard G. (Cancer Research UK, 2013)
Background: Central nervous system primitive neuroectodermal tumours (CNS PNETs) are embryonal tumours occurring predominantly in children. Current lack of knowledge regarding their underlying biology hinders development of more effective treatments. We previously identified WNT/β-catenin pathway activation in one-third of CNS PNETs, which was potentially linked to a better prognosis. In this study, we have extended our cohort, achieving a statistically significant correlation with prognosis. We additionally investigated the biological effects of WNT/β-catenin pathway activation in tumour pathogenesis. Methods: A total of 42 primary and 8 recurrent CNS PNETs were analysed for WNT/β-catenin pathway status using β-catenin immunohistochemistry. Genomic copy number and mRNA expression data were analysed to identify a molecular profile linked to WNT/β-catenin pathway activation. results: Pathway activation was seen in 26% of CNS PNETs and was significantly associated with longer overall survival. Genes displaying a significant difference in expression levels, between tumours with and without WNT/β-catenin pathway activation, included several involved in normal CNS development suggesting aberrant pathway activation may be disrupting this process. conclusion: We have identified WNT/β-catenin pathway status as a marker, which could potentially be used to stratify disease risk for patients with CNS PNET. Gene expression data suggest pathway activation is disrupting normal differentiation in the CNS.